The changing law of the employment relationship : comparative analyses in the European context - Countouris, Nicola (Ashgate, 2015)
Industrialized countries have witnessed a progressive crisis of the regulatory framework sustaining the binary model of the employment relationship based on the subordinate employment/autonomous self-employment dichotomy. This volume provides a comparative account of the development of the employment relationship in four key European countries - the UK, Germany, France and Italy.